Gestational age at birth and type 1 diabetes in childhood and young adulthood : a nationwide register study in Finland, Norway and Sweden - Metsälä, Johanna (Springer Nature, 2025)
Aims/hypothesis: Children and adults born preterm have an increased risk of type 1 diabetes. However, there is limited information on risk patterns across the full range of gestational ages, especially after extremely preterm birth (23-27 weeks of gestation). We investigated the risk of type 1 diabetes in childhood and young adulthood across the full range of length of gestation at birth.
Methods: Data were obtained from national registers in Finland, Norway and Sweden. In each country, information on study participants and gestational age was collected from the Medical Birth Registers, information on type 1 diabetes diagnoses was collected from the National Patient Registers, and information on education, emigration and death was collected from the respective national register sources. Individual-level data were linked using unique personal identity codes. The study population included all individuals born alive between 1987 and 2016 to mothers whose country of birth was the respective Nordic country. Individuals were followed until diagnosis of type 1 diabetes, death, emigration or end of follow-up (31 December 2016 in Finland, 31 December 2017 in Norway and Sweden). Gestational age was categorised as extremely preterm (23-27 completed weeks), very preterm (28-31 weeks), moderately preterm (32-33 weeks), late preterm (34-36 weeks), early term (37-38 weeks), full term (39-41 weeks; reference) and post term (42-45 weeks). HRs and 95% CIs from country-specific covariate-adjusted Cox regression models were combined in a meta-analysis using a common-effect inverse-variance model.
Results: Among 5,501,276 individuals, 0.2% were born extremely preterm, 0.5% very preterm, 0.7% moderately preterm, 4.2% late preterm, 17.7% early term, 69.9% full term, and 6.7% post term. A type 1 diabetes diagnosis was recorded in 12,326 (0.8%), 6364 (0.5%) and 16,856 (0.7%) individuals at a median age of 8.2, 13.0 and 10.5 years in Finland, Norway and Sweden, respectively. Individuals born late preterm or early term had an increased risk of type 1 diabetes compared with their full-term-born peers (pooled, multiple confounder-adjusted HR 1.12, 95% CI 1.07, 1.18; and 1.15, 95% CI 1.11, 1.18, respectively). However, those born extremely preterm or very preterm had a decreased risk of type 1 diabetes (adjusted HR 0.63, 95% CI 0.45, 0.88; and 0.78, 95% CI 0.67, 0.92, respectively). These associations were similar across all three countries.
Conclusions/interpretation: Individuals born late preterm and early term have an increased risk of type 1 diabetes while individuals born extremely preterm or very preterm have a decreased risk of type 1 diabetes compared with those born full term.